Examining the PALSAR-2 Global forest/non-forest maps through Turkish afforestation practices - Altunel, Arif Oguz; Akturk, Emre; Altunel, Tayyibe (Informa UK Limited, 2020)
Forests and afforestation have significant importance, given the present course of World’s climate resulting from our insensitive behaviours, policies, ambitions, etc. Turkish Forest Service has de...
Keywords: 13. Climate action; 15. Life on land